2008
DOI: 10.1096/fj.08-113902
|View full text |Cite
|
Sign up to set email alerts
|

A splice variant of the SLC28A3 gene encodes a novel human concentrative nucleoside transporter‐3 (hCNT3) protein localized in the endoplasmic reticulum

Abstract: Nucleoside transporters are plasma membrane proteins essential for nucleoside salvage. Among them, human concentrative nucleoside transporter 3 (hCNT3, SLC28A3) plays an essential role in this process because of its broader substrate selectivity and higher concentrative ability than the other members of the SLC28 protein family, hCNT1 and hCNT2. The aim of this study was to characterize an isoform of hCNT3, encoded by an alternatively spliced SLC28A3-related mRNA, the first identified for a CNT protein. This v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 54 publications
4
41
0
Order By: Relevance
“…Although the degradation pathways of equilibrative and concentrative nucleoside transporters are largely unknown, an earlier study has shown the third member of the concentrative nucleoside transporter family (hCNT3) is not sensitive to inhibition by a proteasomal inhibitor (MG132) (15). Consistently, our studies identified the degradation of hENT3 to be predominantly via the lysosomal pathway and not the proteasomal pathway.…”
Section: Discussionsupporting
confidence: 86%
“…Although the degradation pathways of equilibrative and concentrative nucleoside transporters are largely unknown, an earlier study has shown the third member of the concentrative nucleoside transporter family (hCNT3) is not sensitive to inhibition by a proteasomal inhibitor (MG132) (15). Consistently, our studies identified the degradation of hENT3 to be predominantly via the lysosomal pathway and not the proteasomal pathway.…”
Section: Discussionsupporting
confidence: 86%
“…Nucleoside-specific membrane transporters mediate plasma membrane permeation of physiologic nucleosides and most nucleoside analogs, which will be further activated intracellularly by nucleoside kinases Huber-Ruano and Pastor-Anglada, 2009;Molina-Arcas et al, 2009). Among these transporters, hCNT3 seems to play a crucial role in the disposition of physiological nucleosides and nucleoside analogs because of its broad substrate selectivity, high concentrative capacity, and relatively wide tissue distribution Errasti-Murugarren et al, 2009). In absorptive epithelia, apical localization of hCNT3 is crucial to determine vectorial flux of all antiviral and anticancer nucleosides tested so far (Errasti-Murugarren et al, 2007), thus being a major candidate to modulate drug pharmacokinetics.…”
Section: Introductionmentioning
confidence: 99%
“…hCNT3ins lacks the first 69 amino acids of the cytoplasmic N terminus, seems to be the result of alternative splicing of the SLC28A3 gene, and is retained intracellularly at the endoplasmic reticulum when expressed in nonpolarized cells (Errasti-Murugarren et al, 2009). Expression in polarized MDCK cells also reveals a loss of fidelity for apical sorting (Errasti-Murugarren et al, 2009). These findings anticipate that the N terminus of hCNT3 is implicated in protein trafficking in both polarized and nonpolarized cells.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a splice variant of human concentrative nucleoside transporter 3 was localized exclusively to the endoplasmic reticulum where it was shown to mediate the accumulation of nucleosides and nucleobases (34). Our finding that PfNT2 localizes to the ER is a first for a member of the ENT family and suggests a novel role for this organelle in parasite biology.…”
Section: Discussionmentioning
confidence: 64%
“…The concept of the ER accumulating nucleosides and nucleobases is supported by the recent localization of a hCNT3 splice variant to this organelle (34). In some lower eukaryotes, specialized organelles and specific transport proteins mediate detoxification processes for compounds such as transition metals and purine analogs (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%